THE EFFECT OF SAKYO STYLE EXERCISES (SAQ) ON DEVELOPING SOME MOTOR AND SKILL ABILITIES AMONG YOUNG FOOTBALL PLAYERS IN MISAN GOVERNORATE - Dheyaa Salim Hafedh (Journal Park Publishing, 2023)
Sakyo exercises are a modern training method that simulates relatively great muscular effort, which stimulates muscle groups in mobilising the largest possible number of muscle fibres and possesses the property of rapid muscle contraction, which raises it to work at a high level by emphasising speed and interactive agility. This, in turn, contributes to the development of specific physical and skill abilities by producing the required strength that helps in completing the skill as required and improving skill performance, which plays a significant role in controlling the player's performance in these skills required during football. This, in turn, contributes to the development of certain physical and skill abilities by producing the required strength that helps in completing the skill as required and improving skill performance, which plays a significant role in controlling the player's performance in these skills required during football. This helps the team achieve the best results in matches. Through the researcher's follow-up as a former Iraqi league player and youth coach, he noticed that some players' physical and skill abilities in applying special skills in football are weak. This helps the team achieve the best results in matches. Through the researcher's follow-up as a former Iraqi league player and youth coach, he noticed that some players' physical and skill abilities in applying special skills in football are weak. Identify the effect of Sakyo training on the motor and skill abilities of young football players in the experimental group between pre- and post-tests because the Sakyo style exercises employed by the researcher have a positive effect on the development of the physical and skill abilities of young football players. Identify the effect of Sakyo training on the motor and skill abilities of young football players in the experimental group between pre- and post-tests because the Sakyo style exercises employed by the researcher have a positive effect on the development of the physical and skill abilities of young football players.